Fertilization, Oocyte Activation, Calcium Release and Epigenetic Remodelling: Lessons From Cancer Models - Shafqat, Areez; Kashir, Junaid; Alsalameh, Sulaiman; Alkattan, Khaled; Yaqinuddin, Ahmed (Frontiers in Cell and Developmental Biology, 2022)
Oocyte activation deficiency (OAD) is the basis of Total Fertilisation Failure (TFF) and is attributed to mutations in the PLCζ gene—termed male factor infertility. This derives abnormal Ca2+ oscillations and could be the main cause of primary disruptions in the gene expression of Ca2+-related proteins. Epigenetic mechanisms are universally accepted as key regulators of gene expression. However, epigenetic dysregulations have not been considered as potential mechanisms of oocyte-borne OAD. Herein, we discuss changes in the DNA methylome during oogenesis and embryogenesis. We further highlight key pathways comprising the oocyte Ca2+ toolkit, which could be targets of epigenetic alterations, especially aberrations in DNA methylation. Considering that the vast majority of epigenetic modifications examined during fertilization revolve around alterations in DNA methylation, we aim in this article to associate Ca2+-specific mechanisms with these alterations. To strengthen this perspective, we bring evidence from cancer research on the intricate link between DNA methylation and Ca2+ signaling as cancer research has examined such questions in a lot more detail. From a therapeutic standpoint, if our hypothesis is proven to be correct, this will explain the cause of TFF in idiopathic cases and will open doors for novel therapeutic targets.